Re-evaluation of hematocrit as a determinant of thrombotic risk in erythrocytosis - Gordeuk, Victor R. (Haematologica, 2019)
Here we critically evaluate the role of elevated hematocrit as the principal determinant of thrombotic risk in polycythemia and erythrocytosis, defined by an expansion of red cell mass. Since red cell volume determination is no longer readily available, in clinical practice, polycythemia and erythrocytosis are defined by elevated hemoglobin and hematocrit. Thrombosis is common in Chuvash erythrocytosis and polycythemia vera. Although the increased thrombotic risk is assumed to be due to the elevated hematocrit and an associated increase in blood viscosity, thrombosis does not accompany most types of erythrocytosis. We review studies indicating that the occurrence of thrombosis in Chuvash erythrocytosis is independent of hematocrit, that the thrombotic risk is paradoxically increased by phlebotomy in Chuvash erythrocytosis, and that, when compared to chemotherapy, phlebotomy is associated with increased thrombotic risk in polycythemia vera. Inherited and environmental causes that lead to polycythemia and erythrocytosis are accompanied by diverse cellular changes that could directly affect thrombotic risk, irrespective of the elevated hematocrit. The pressing issue in these disorders is to define factors other than elevated hematocrit that determine thrombotic risk. Defining these predisposing factors in polycythemia and erythrocytosis should then lead to rational therapies and facilitate development of targeted interventions.